'Arms and Wages', 1941 (1941)
1941 1939-1945 "'Arms and Wages', 1941" [HFR0074], 1941 In this pamphlet, published by the Amalgamated Engineering Union in 1941, Jack Tanner [the AEU President] sets out the engineers' case for an increase of 4d per hour on basic rates.